(untitled) (KYAMC Journal, 2022)
Background: Burkholderia cepacia complex (Bcc) bacteria are endowed with an extraordinary metabolic diversity and emerged in the 1980s as life-threatening and difficult-to-treat pathogens among the patients suffering from cystic fibrosis (CF). Recently, these bacteria became recognized as a threat to hospitalized patients suffering from other diseases, in particular oncological patients. Objectives: The objectives of the present study were to isolate, speciate, reactions to different substrates and to find out the antibiogram of Bcc from different clinical samples. Materials and Methods: These Gram negative organisms were analyzed by BD Phoenix M50 Automated Microbiology System for carbohydrates, amino acids and proteins and other substrates to observe the reactions. Antibiogram was also observed. Results: Reactions to different substrates showed similarities with other studies with some variations. Antimicrobial susceptibility pattern of the Bcc isolates was found almost similar in comparison to other studies with some differences. Conclusion: Bcc demands an early detection and diagnosis as the incidences of infection by these organisms are increasing day by day. Therefore, this automated system can be used as a tool to facilitate early identification and antimicrobial susceptibility pattern of the Bcc bacteria in routine microbiology laboratories. KYAMC Journal Vol. 13, No. 01, April 2022: 4-8